Coring method of sampling potato tubers to detect ralstonia solanacearum - Okiro, L.A.; Nyanjom, S.G.; Parker, M. (Sciencedomain International, 2016)
Bacterial wilt caused by Ralstonia solanacearum is considered among the most damaging diseases of potato in Sub-Saharan Africa. In Kenya, majority of farmers visually select and save seed from harvested potato tubers and reuse the same tubers for several seasons. Latently infected seed tubers which cannot be identified by visual inspection during certification further compounds the situation compelling the need for laboratory testing. The study evaluated the effectiveness of coring tuber samples to improve sampling efficiency for onward laboratory diagnosis. In this study, the coring method of sampling potato tubers for detection R. solanacearum was evaluated. Coring involves taking multiple tuber samples direct from the stolon attachment site into a collection tube containing extraction buffer that provides the extract for further diagnostic tests. Coring was assessed using field samples from different potato growing regions of Kenya including, Koibatek, Molo, Uasin Gishu, Bungoma and Kisii and tested using Nitrocellulose Membrane (NCM) ELISA. These results were compared to PCR, qPCR and LAMP. Coring method was statistically reliable (p>0.05) when compared to the standard sampling method used in Kenya to detect R. solanacearum. The coring of potato tubers is a reliable and quicker method of sampling that reduces the turnaround time of testing hence improving efficiency.